Hamas and the 'trap' of sectarianism?. Issue 4 (1st October 2016) - Musgrave, Nina
ABSTRACT: This article addresses Hamas's reaction to increased sectarian tensions in the Middle East following the outbreak of the Arab Spring. More specifically, it addresses Hamas's response to the development of the Syrian civil war and its political bureau's decision to vacate its Syrian headquarters. It is argued that Hamas has shown a disinclination towards sectarianism for both pragmatic and ideological reasons, and this is partly related to how Hamas conceives its place within the 'Islamist family', its identification with other groups; what Hamas would call 'national liberation movements' and a desire to maintain operational and ideological independence.